جمالية الفن الإسلامي - محمودي، ذهبية (جامعة شريف هداية الله الإسلامية الحكومية - كلية الدراسات الإسلامية والعربية, 2020)
إن بحث جمالية الفن الإسلامي، بحث تحليلي لأهم مميزاته، لكونه مرتبطا بالعقيدة الإسلامية، حيث أجريت حوله دراسات عديدة، حاولت التشكيك في أصالته وتفرده عن باقي الفنون التي عاصرته أو سبقته، وحاولت في كل مرة أن ترجع إبداعاته وجماليته إلى فنون أخرى، غير أن دراسته دراسة فلسفية وفكرية، جعلنا نتوصل في نهاية البحث، أن الفن الإسلامي من أوسع، وأن المنهج الفكري للعقيدة الإسلامية كان له بصماته الواضحة على أشكاله ومضامينه على مختلف الفنون، وخلاصة القول: إن جمالية الفن الإسلامي بلورته العقيدة الإسلامية، رغم عاملي التأثر والتأثير.
The study of Islamic art is an analytical study of its most important features, as it is linked to the Islamic faith. Many studies were conducted around it, which attempted to question its originality and uniqueness from the rest of the arts that were contemporary to it or preceded it, and tried every time to refer its creativity and aesthetics to other arts. However the study of this unique art is a philosophical and intellectual study. At the end of the research, we reached the conclusion that Islamic art is one of the broadest arts, and that the intellectual approach of the Islamic faith had its clear imprint on its forms and contents on various arts. To sum up, the aesthetic of Islamic art was crystallized by the Islamic faith, despite the factors of influence and being influenced.
Keywords: الفن الإسلامي -- القيم الجمالية -- العقيدة الإسلامية -- الآثار الإسلامية